Distribution and inventory planning in multi-echelon supply chains under demand uncertainty. (23rd January 2023) - Vicente, Joaquim Jorge; Relvas, Susana; Barbosa-Póvoa, Ana Paula
Distribution and inventory planning in a multi-echelon system are studied under an uncertain demand context. To deal with this problem a mixed integer linear programming (MILP) model is proposed. This considers a multi-echelon system formed by N-warehouses and M-retailers. The problem consists on determining the optimal reordering plan for the operating network, which minimises the overall system's operation cost. The uncertain demand faced by retailers is addressed by defining the optimal safety stock that guarantees a given service level at each regional warehouse and each retailer. Also, the risk pooling effect is taken into account when determining inventory levels in each entity. A case study based on a real retailer distribution chain is presented and solved.